Real-World Effectiveness and Safety of Insulin Glargine 300 U/mL in Patients with T2D Uncontrolled on NPH or Premixed Insulins as Part of Routine Clinical Practice in Bulgaria: ToUPGRADE Study - Kamenov, Zdravko (Diabetes Ther, 2021)
INTRODUCTION: The aim of this study is to demonstrate the real-life effectiveness and safety of insulin glargine 300 U/mL (Gla-300) in patients with type 2 diabetes (T2D) previously uncontrolled on NPH ± prandial insulin or premixed insulins in routine clinical practice in Bulgaria. METHODS: This was a 24-week prospective, observational study performed in 40 inpatient and outpatient sites across the country. RESULTS: A total of 286 patients were included in the study. The mean age (± SD) was 61.2 ± 10.0 years with duration of diabetes of 11.64 ± 7.5 years and body mass index (BMI) of 32.1 ± 5.7 kg/m(2). HbA1c before Gla-300 initiation was 9.8 ± 1.0%, and fasting plasma glucose (FPG) was 13.1 ± 3.4 mmol/L. HbA1c and FPG change from baseline to week 24 was − 1.86% (p < 0.001) and − 4.8 mmol/L (p < 0.001), respectively. The proportion of patients reaching their individualized HbA1c at week 24 was 39.1% (95% CI 33.3–45.1%), while the proportion of patients reaching their individualized HbA1c target without confirmed and/or severe hypoglycaemia was 34.8% (95% CI 29.2–40.7%). At study end, 19.0% (95% CI 14.6–24.1%) achieved HbA1c < 7%. Body weight decreased from 88.3 to 87.0 kg from baseline to week 24 with mean change of − 1.3 kg (p < 0.001). The incidence and event rates of anytime confirmed (≤ 3.9 mmol/L) and/or severe hypoglycaemia were low: 7.7% and 0.42 events per patient-year, respectively. The overall Insulin Treatment Satisfaction Questionnaire (ITSQ) score increased from 53.2 to 78.2 from baseline to week 24 and the difference of 25.1 ± 21.5 points was significant (p < 0.001). CONCLUSIONS: In real-life settings, Gla-300 significantly improved glycaemic control and insulin treatment satisfaction in people with T2D who were inadequately controlled with NPH ± prandial insulin or premixed insulin analogues. Improvement of glycaemic control was associated with a very low risk of hypoglycaemia and with significant weight loss irrespective of the previous insulin regimen. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13300-021-01022-0.